Imagem e discurso: dois lados de uma mesma moeda: uma abordagem semi??tica da comunica????o na Caixa Econ??mica Federal - Codevila, Juliana Senna (2015)
This current work uses the case of an actual company, in proven growth, to further studies on Organizational Communication. The study examined the main expressions that "Caixa Economica Federal" seeks to communicate to its receptors, through its discourse and the main impressions the same receptors have about the company, when submitted to their discursive texts. The work was divided, for better comprehension, in chapters on Organizational Communication, Discourse, Image, Research Analysis and Conclusion. The study analyzed if there is consonance or dissonance between the message that is relayed and the message that is received. The analysis takes place through diverse data, from the last few years, on the company, in addition to image research made and provided by the Institution, focusing on ad campaigns, spokespersons, athletic sponsorships, and semiotic analysis on the main texts of the institution, selected by the author. Outside research on client satisfaction regarding bank services were also utilized with the purpose of comparison. To analyze the results, the Semiotics theory of Pierce was used. In the end of this dissertation we may conclude that the company needs to improve the structure of its communication department to then, improve its communication, and even though it is on the right path towards long term growth, it is necessary to revisit some strategic definitions such as sponsorship amounts, spokespersons, communication strategic planning, among others, aiming to maintain, or even increase, its market share and and solve the issues detected in this dissertation.